2019
DOI: 10.7717/peerj.6489
|View full text |Cite
|
Sign up to set email alerts
|

Alternative reproductive strategies in black-winged territorial males ofParaphlebia zoe(Odonata, Thaumatoneuridae)

Abstract: Alternative reproductive strategies are commonly associated with male dimorphism. In Paraphlebia zoe, a species of damselfly whose males are dimorphic in wing coloration, black-and-white-winged (BW) males defend territories, while hyaline-winged (HW) males usually play the role of satellites. We found that several BW males can sometimes share a territory, and we hypothesized that within this morph there are two alternative tactics: submissive and dominant. We conducted an experiment to test whether dominant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…wing spots). These are often considered 'honest' sexual signals that indicate the quality of a territorial male [15][16][17][18], but whether the size of these wing spots correlates with the success of holding a territory is so far inconclusive [19,20]. Furthermore, the possibility to implement modern phylogenetic analysis on an already existing dataset of odonate territory size [11] provided the stimulus for the current study.…”
Section: Introductionmentioning
confidence: 99%
“…wing spots). These are often considered 'honest' sexual signals that indicate the quality of a territorial male [15][16][17][18], but whether the size of these wing spots correlates with the success of holding a territory is so far inconclusive [19,20]. Furthermore, the possibility to implement modern phylogenetic analysis on an already existing dataset of odonate territory size [11] provided the stimulus for the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Though less common, there are also cases of male‐limited polymorphism in odonates (e.g., Mnais andersoni , Mnais costalis , Paraphlebia quinta ) (Hooper et al., 1999; Romo‐Beltrán et al., 2009). Diversity of color traits in polymorphic species is usually associated with certain behaviors in individuals (e.g., territoriality), which do not change when the color of an individual is modified experimentally (Rivas‐Torres et al., 2019), but such modification can elicit different responses from conspecifics (Beatty et al., 2015).…”
Section: Adult Color Variationmentioning
confidence: 99%
“…Of these studies, the Orders of Carnivora [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], Cetacea [ 10 , 46 ] and primates [ 18 ], particularly chimpanzees ( Pan troglodytes) [ 58 , 59 , 60 , 61 ] were the most commonly studied groups. While reptile [ 62 , 63 , 64 ], bird, fish [ 65 ] and invertebrate [ 66 , 67 ] species appeared in some studies, they were in the minority overall. No studies of behavioral diversity in amphibians were identified.…”
Section: Comparison Of Indicesmentioning
confidence: 99%